NILAI-NILAI PENDIDIKAN ISLAM PERSPEKTIF SYEKH HASAN DIMEJO DALAM MANUSKRIP HAQQUL ISLAM - Ramadhan, Syahrul; Alam, Mufassirul (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2025)
This study reveals that Sheikh Hasan Dimejo, through his manuscript Haqqul Islam, articulates a comprehensive framework of Islamic educational values structured into three interrelated domains. First, the faith-based values emphasize obedience to divine commandments and avoidance of prohibitions, fostering taslim — complete submission — to strengthen faith. This includes vigilance against actions that contradict Islamic principles and awareness of Satan’s deceptions. Second, the worship-related values underscore the precedence of obligatory duties over supererogatory acts. Sheikh Hasan promotes learning from scholars with deep mastery of Islamic jurisprudence, encourages the performance of righteous deeds that benefit society, and highlights the importance of seeking a lawful and beneficial livelihood. Third, the moral values stress the ethical dimension of Islamic education, such as promoting social solidarity, refraining from injustice, and upholding mutual respect in interpersonal relations. Altogether, these values reflect a holistic vision of Islamic education that integrates belief, worship, and character development, aiming to shape individuals who are spiritually grounded, socially responsible, and morally upright.